International law, intervention and United Nations peacekeeping in the Democratic Republic of the Congo - Giblin, Jennifer (2021)
Is peacekeeping intervention? This is the central theme which runs throughout this thesis. Since its conception in the mid-1950s, peacekeeping has significantly evolved from traditional, passive, monitoring and observing operations to robust, multi-dimensional stabilisation operations. This raises questions as to whether this is simply a natural evolution of peacekeeping or whether it marks an expansion of the concept of peacekeeping beyond its boundaries, pushing it into the realm of peace enforcement or intervention. Put simply, has peacekeeping evolved too far?